Enzymatic hydrolysis of defatted soy flour by three different proteases and their effect on the functional properties of resulting protein hydrolysates - M. Hrčková; M. Rusňáková; J. Zemanovič (Czech Journal of Food Sciences, 2002)
Commercial defatted soy flour (DSF) was dispersed in distilled water at pH 7 to prepare 5% aqueous dispersion. Soy protein hydrolysates (SPH) were obtained by enzymatic hydrolysis of the DSF using three different proteases (Flavourzyme 1000 L, No-vozym FM 2.0 L and Alcalase 2.4 L FG). The highest degree of hydrolysis (DH 39.5) was observed in the presence of protease Flavourzyme. SPH were used for measuring functional properties (foaming stability, gelation). Treatment with Flavourzyme improved foaming of proteins of DSF. Foaming stability was low in the presence of Novozym. Proteases treated DSF showed good gelation properties, mainly in the case of treatment with Flavourzyme. SDS-PAGE analysis showed that after enzyme ad-dition to the 5% aqueous dispersion of DSF each enzyme degraded both b-conglycinin and glycinin. In general, the basic polypeptide from glycinin showed the highest resistance to proteolytic activity. The most abundant free amino acids in the hydrolysates were histidine (30%), leucine (24%) and tyrosine (19%) in the case of the treatment with proteases Alcalase and Novozym, and arginine (22.1%), leucine (10.6%) and phenylalanine (12.9%) in the case of the treatment with Flavourzyme.